Identification of Immune-Relevant Factors Conferring Sarcoidosis Genetic Risk - Fischer, Annegret; Ellinghaus, David; Nutsua, Marcel; Hofmann, Sylvia; Montgomery, Courtney G; Iannuzzi, Michael C; Rybicki, Benjamin A; Petrek, Martin; Mrazek, Frantisek; Pabst, Stefan; Grohé, Christian; Grunewald, Johan; et al. (American journal of respiratory and critical care medicine, 2015)
RATIONALE: Genetic variation plays a significant role in the etiology of sarcoidosis. However, only a small fraction of its heritability has been explained so far. OBJECTIVES: To define further genetic risk loci for sarcoidosis, we used the Immunochip for a candidate gene association study of immune-associated loci. METHODS: Altogether the study population comprised over 19,000 individuals. In a two-stage design, 1,726 German sarcoidosis cases and 5,482 control subjects were genotyped for 128,705 single-nucleotide polymorphisms using the Illumina Immunochip for the screening step. The remaining 3,955 cases, 7,514 control subjects, and 684 parents of affected offspring were used for validation and replication of 44 candidate and two established risk single-nucleotide polymorphisms. MEASUREMENTS AND MAIN RESULTS: Four novel susceptibility loci were identified with genome-wide significance in the European case-control populations, located on chromosomes 12q24.12 (rs653178; ATXN2/SH2B3), 5q33.3 (rs4921492; IL12B), 4q24 (rs223498; MANBA/NFKB1), and 2q33.2 (rs6748088; FAM117B). We further defined three independent association signals in the HLA region with genome-wide significance, peaking in the BTNL2 promoter region (rs5007259), at HLA-B (rs4143332/HLA-B*0801) and at HLA-DPB1 (rs9277542), and found another novel independent signal near IL23R (rs12069782) on chromosome 1p31.3. CONCLUSIONS: Functional predictions and protein network analyses suggest a prominent role of the drug-targetable IL23/Th17 signaling pathway in the genetic etiology of sarcoidosis. Our findings reveal a substantial genetic overlap of sarcoidosis with diverse immune-mediated inflammatory disorders, which could be of relevance for the clinical application of modern therapeutics.
Keywords: senioři; běloši; Genetic Markers; Genetic Predisposition to Disease; association; celogenomová asociační studie; genotyp; jednonukleotidový polymorfismus; HLA; Male; Europe; Sarcoidosis; Genotype; Evropa; Middle Aged; černoši nebo Afroameričané; mužské pohlaví; studie případů a kontrol; Adult; IL23; BTNL2; ženské pohlaví; Humans; Black or African American; sarkoidóza; lidé středního věku; White People; dospělí; genetická predispozice k nemoci; Female; Aged; genetické markery; Genome-Wide Association Study; Immunochip; lidé; Case-Control Studies; Polymorphism, Single Nucleotide